Supporting Students in the Classroom: Training Paraprofessionals to Teach Self- Advocacy and Self-Determination Skills - Tse, Courteney Mayumi; Pierson, Melinda R. (Kultura-Społeczeństwo-Edukacja, 2019)
Students with disabilities lack the skills to become independent self-advocates. This article details a training program that was implemented for paraprofessionals who support students with disabilities in public school classrooms in the United States. Results indicated that advanced training of paraprofessionals improved student support which led to greater independence for the students with disabilities.